HOW DOES INTERPRETATION COMBINE WITH THE NON-VERBAL ASPECTS OF COMMUNICATION? - Clara Cunha, Maria (2019)
This paper aims at bringing forth the major role of nonverbal communication within the interpreting domain as well as to assess the main difficulties that stem from the way it is combined with verbal language.A set of the most critical and frequent nonverbal resources is outlined, together with a few suggestions of how/when they can be integrated in interpreting tasks.